2019
DOI: 10.1101/811737
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide association study of gastrointestinal disorders reinforces the link between the digestive tract and the nervous system

Abstract: 11Genetic factors are recognized to contribute to common gastrointestinal (GI) diseases such as gastro-12 oesophageal reflux disease (GORD), peptic ulcer disease (PUD), irritable bowel syndrome (IBS) and 13 inflammatory bowel disease (IBD). We conducted genome-wide association analyses based on 456,414 14 individuals and identified 27 independent and significant loci for GORD, PUD and IBS, including SNPs 15 associated with PUD at or near genes MUC1, FUT2, PSCA and CCKBR, for which there are previously 16 estab… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 104 publications
1
8
0
Order By: Relevance
“…We found a causal effect of GERD on endometriosis as well as a bidirectional causal relationship between depression and GERD. The finding for depression and GERD agrees not only with a previous observational study (Kim et al 2018) but also a recent GWAS analysis (Wu et al 2019). Hence, causality may indeed explain the comorbidity of depression with GERD.…”
Section: Discussionsupporting
confidence: 91%
“…We found a causal effect of GERD on endometriosis as well as a bidirectional causal relationship between depression and GERD. The finding for depression and GERD agrees not only with a previous observational study (Kim et al 2018) but also a recent GWAS analysis (Wu et al 2019). Hence, causality may indeed explain the comorbidity of depression with GERD.…”
Section: Discussionsupporting
confidence: 91%
“…This implies that the relationship between GERD and BE cannot be solely explained by a common direct effect of obesity. Formal Mendelian randomisation (MR) analyses have been attempted previously 38 ; however, interpreting the results from such studies is difficult given we have shown that there are at least two pathways leading to GERD (one acting via obesity associated SNPs, another acting via depression SNPs).…”
Section: Discussionmentioning
confidence: 99%
“…When examining nervous system disorders separately, this pattern of aetiological influences was seen for sleep disorders, whereas the correlation between ADHD and migraine was almost completely explained by genetic factors. Significant phenotypic correlations were also observed between ADHD and metabolic, respiratory, and musculoskeletal disease groups (0•14-0•16); genetic factors explained 60-69% of correlations and the remainder was explained by non-shared environmental factors (figure 2; appendix pp [15][16][17].…”
Section: Role Of the Funding Sourcementioning
confidence: 99%
“…The few available quantitative and molecular genetic studies have revealed weak-to-moderate genetic associations between ADHD and conditions such as obesity, diabetes, asthma, epilepsy, and migraines. 6 , 16 , 17 , 18 Further research, using statistically high-powered methods and a broader range of diseases across adulthood, is needed to understand the aetiological processes underlying the increased occurrence of physical conditions in people with ADHD.…”
Section: Introductionmentioning
confidence: 99%